The influence of geographical area on morphometric parameters of the honey bee in Serbia - Ignjatović Aleksandar; Matović Kazimir; Jevtić Goran; Nedić Nebojša (Agroznanje, 2024)
In this study, morphological characteristics were measured on worker honey bee samples collected from seven different locations covering the territory of the Republic of Serbia. Three samples were taken from the territory of AP Vojvodina, namely from the Southern Banat District (Vršac; I), the South Bačka District (Bač; II), and the West Bačka District (Crvenka; III). The worker bees from the central Serbia originated from different sites namely, the Rasina District (Aleksandrovac; IV), the Zlatibor District (Lučani; V), Pešter (Sjenica; VI), and the Bor District (Negotin; VII). From each sample, 15 bees were randomly selected, and their front right wings were dissected and mounted on slides in two rows. After wing preparation, they were scanned using an Epson Perfection V600 Photo scanner with a resolution of 4800 dpi. The measurement included a total of 14 parameters, 11 of which were the angles on the forewing, while the other parameters analyzed were the forewing length and width and the cubital index. The results have shown that there is a high statistically significant difference between the localities in the characteristics examined in this study. From a total of 11 angles analyzed, statistical significance (p<0.01) of average values between the localities was determined for the following angles: A4, J16, K19, L13, N23, G18, and O26. The analysis of the results of the front wings length and the cubital index has shown a significant difference between the groups of honey bees. The average forewing length across all locations in the study was 9.17mm, while the average forewing width was 3.43. The difference in terms of the average forewing width was not statistically significant between the locations. The values of the cubital index ranged from 2.28 to 2.79, with an average of 2.49 across all locations.